Physiological and Immunological Causes of the Susceptibility of Chronic Inflammatory Patients to COVID-19 Infection: Focus on Diabetes - Rahmani-Kukia, Nasim; Abbasi, Ardeshir (Frontiers in Endocrinology, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has recently emerged, which was then spread rapidly in more than 190 countries worldwide so far. According to the World Health Organization, 3,232,062 global cases of COVID-19 were confirmed on April 30th with a mortality rate of 3.4%. Notably, the symptoms are almost similar to those of flu such as fever, cough, and fatigue. Unfortunately, the global rates of morbidity and mortality caused by this disease are more and still increasing on a daily basis. The rates for patients suffering from inflammatory diseases like diabetes, is even further, due to their susceptibility to the pathogenesis of COVID-19. In this review, we attempted to focus on diabetes to clarify the physiological and immunological characteristics of diabetics before and after the infection with COVID-19. We hope these conceptions could provide a better understanding of the mechanisms involved in COVID-19 susceptibility and increase the awareness of risk to motivate behavior changes in vulnerable people for enhancing the prevention. Up to now, the important role of immune responses, especially the innate ones, in the development of the worst signs in COVID-19 infection have been confirmed. Therefore, to better control patients with COVID-19, it is recommended to consider a history of chronic inflammatory diseases as well as the way of controlling immune response in these patients.